Reverberation Mapping of Two Variable Active Galactic Nuclei: Probing the Distinct Characteristics of the Inner and Outer Broad-line Regions - Hai-Cheng Feng; Sha-Sha Li; J. M. Bai; H. T. Liu; Kai-Xing Lu; Yu-Xuan Pang; Mouyuan Sun; Jian-Guo Wang; Yerong Xu; Yang-Wei Zhang; Shuying Zhou (The Astrophysical Journal, 2025)
Current reverberation mapping (RM) studies primarily focus on single emission lines, particularly the H β line, which may not fully reveal the geometry and kinematic properties of the broad-line region (BLR). To overcome this limitation, we have conducted multiline RM observations on two highly variable active galactic nuclei (AGNs), KUG 1141+371 and UGC 3374, using the Lijiang 2.4 m telescope. Our goal was to investigate the detailed structures of different regions within the BLR. We measured the time lags of multiple broad emission lines (H α , H β , H γ , He i , and He ii ) and found clear evidence of radial ionization stratification in the BLRs of both AGNs. Velocity-resolved RM analysis revealed distinct geometry and kinematics between the inner and outer regions of the BLRs. Assuming that the velocity-resolved lags reflect the kinematics of the BLR, our observations indicate that: (1) in KUG 1141+371, the inner BLR exhibits outflow signatures, while the outer region is consistent with virialized motion; and (2) in UGC 3374, the inner region displays virial motion, while the outer region shows inflow. Furthermore, we detected “breathing” behavior in the outer BLR regions of both AGNs, while the inner BLR regions show “anti-breathing,” which may be linked to intrinsic BLR properties. We discuss these findings in the context of various BLR formation models, highlighting the importance of long-term, multiline RM campaigns in understanding of BLR structure and evolution. Additionally, our results suggest that the observed stratification in BLR geometry and kinematics may contribute to the scatter in black hole mass estimates and the rapid changes in velocity-resolved RM signatures reported in recent studies.